IMMIGRATION AND XENOPHOBIA IN SAMUEL SELVON’S THE LONELY LONDONERS - Afnane NEDJAI.Nour El Houda NECHE, Dr. Bachir SAHED (université mohamed boudiaf .m'sila, 2023)
ABSTRACT This present study examines Samuel Selvon’s The Lonely Londoners (1956). It explores the characters’ negotiation of cultural hybridity and their strategies for maintaining a sense of self, trying to adapt to a foreign environment. Employing the postcolonial approach to literary criticism, the study analyses how immigration shapes individual and collective identities, as well as how the challenges faced by immigrants in a new cultural context lead to a crisis of belonging. In the light of Edward Said’s Otherness and Homi Bhabha’s notions of hybridity, unhomeliness and mimicry, the study probes into the role xenophobia and discrimination in (re)shaping immigrants’ identities. Thus, the research is made up of two main chapters. The first chapter deconstructs the socio-historical context of the study and establishes the theoretical framework. The second chapter represents the core of the study in which the postcolonial theory is applied.
Keywords: Keywords: alienation; hybridity; identity; immigration; mimicry; otherness; unhomeliness; xenophobia